Influence of Apical Periodontitis on Stress Oxidative Parameters in Diabetic Rats - Prieto, Annelise Katrine Carrara [UNESP]; Gomes-Filho, João Eduardo [UNESP]; Azuma, Mariane Maffei [UNESP]; Sivieri-Araújo, Gustavo [UNESP]; Narciso, Luis Gustavo [UNESP]; Souza, Jucilene Conceição [UNESP]; Ciarlini, Paulo César [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Elsevier, 2017)
Introduction In this study, we investigated if apical periodontitis (AP) associated with diabetes influenced the levels of endogenous antioxidants, the total antioxidant capacity (TAC), and the oxidant parameter in the serum of Wistar rats. Methods Forty male rats were divided into 4 equal groups: normal rats (N), rats with AP (AP), diabetic rats (D), and diabetic rats with AP (D + AP). Diabetes was induced by alloxan (150 mg/kg). AP was induced by exposing the pulpal tissue to the oral environment. After 36 days, blood and maxillae were collected. Albumin, bilirubin, uric acid, TAC, and malondialdehyde (MDA) levels were measured, and histologic analysis of the maxillae was performed. P <.05 was set as the threshold for statistical significance. Results Uric acid levels were higher in the D + AP group when compared with that of the N, D, and AP groups (P <.05). The MDA concentration was higher in the D and D + AP groups when compared with the N and AP groups (P <.05). The level of albumin was lower in the D + AP group when compared with the N, AP, and D groups. Inflammatory infiltration was more intense in the periapical region in the D + AP group compared with that in the AP group (P <.05). Conclusions Our findings indicate that diabetes may change the antioxidant status, increase the concentration of MDA and uric acid, and decrease albumin levels in the serum. In addition, AP can potentiate the effects of diabetes by reducing the levels of albumin and increasing the levels of uric acid.
Keywords: Albumin; apical periodontitis; bilirubin; diabetes mellitus; oxidative stress; uric acid